High beam quality narrow linewidth microsecond pulse Ti:sapphire laser operating at 819.710 nm. (May 2019) - Zong, Qing-Shuang; Bian, Qi; Xu, Chang; Chang, Jin-Quan; He, Li-Jiao; Bo, Yong; Zuo, Jun-Wei; Xu, Yi-Ting; Cui, Da-Fu; Peng, Qin-Jun; Xu, Zu-Yan
Highlights: A high beam quality narrow linewidth μs-pulse Ti:sapphire laser is firstly obtained. Such μs 819.710 nm laser is well suited to generate a polychromatic laser guide star. A 3 W 819.710 nm laser is generated by a frequency-doubled 1064 nm Nd:YAG laser. The laser is operating at 500 Hz repetition rate with pulse width of ∼25 μs. The linewidth of the laser is 0.8 pm with M 2 = 1.14. Abstract: A sub-pm linewidth high beam quality microsecond (μs) Ti:sapphire laser was reported, which was end-pumped by a frequency-doubled 1064 nm Nd:YAG laser. By inserting three birefringent plates tuner and one etalon into the cavity of the Ti:sapphire laser, a ∼ 0.8 pm linewidth at 819.710 nm was achieved with a maximum output power of 3 W operating at a high repetition rate of 500 Hz with pulse width of ∼25 μs. The beam quality factor M 2 was measured to be ∼1.14. The wavelength could be finely tuned from 819.699 to 819.718 nm with tuning resolution of 0.76 pm. To the best of our knowledge, this is the first demonstration on the μs pulse Ti:sapphire laser at 819.710 nm with narrow linewidth and high beam quality simultaneously. Such μs 819.710 nm laser could be used to efficiently generate a polychromatic laser guide star together with a 589 nm laser for the tip-tilt correction of ground-based telescopes.